Economy of modern India 1860-1970 - "Tomlinson , B . R" (London, 1998)
In the first comprehensive and wide-ranging account of the modern Indian economy, B. R. Tomlinson considers the history of economic growth and change over the last hundred years. By summarising and expounding on the available literature, the author considers the debates over imperialism, development and under development and sets them in the context of historical change in agriculture, trade and manufacture, and the relations between business, the economy and the state.
Keywords: India-Economic conditions-1860-1970